Lightlark - Aster, Alex (Aster, Alex. Lightlark saga, 2022)
In order to break a curse on her kingdom, Isla Crown, the young ruler of Wilding, must compete in the Centennial, a deadly game that only the rulers of six realms are invited to play, and to survive she must lie, cheat, and betray--even as love threatens to undo everything.